PENGARUH PROSEDUR PENERJEMAHAN POLA DAN JENIS KALIMAT BAHASA INDONESIA DAN INGGRIS DALAM NOVEL TERJEMAHAN CALON ARANG: SEBUAH ANALISIS KONTRASTIF - Griselda Felicia Fredyryna Tumbole; Sajarwa Roman (Universitas Sebelas Maret, 2022)
The purpose of this study was to examine the effect of translation procedures and types of sentences from Indonesian (BSU) into English (BSA) in Indonesian literary novels by Pramoedya Ananta Toer